Analisis Pembiayaan Bersandi 2 (Dalam Perhatian Khusus) Pada Produk KPR (Kredit Pemilikan Rumah) iB Syariah Tapak Pada PT. Bank Sumut Kantor Cabang Pembantu Syariah H.M Joni Medan - Erna Sipahutar; Nursantri Yanti (STIE Trisna Negara OKU Timur, 2022)
Researchers directly observed at PT. Bank Sumut Sharia Sub-Branch Office H.M Joni Medan. With the object of research, Code 2 for the iB Syariah Tapak KPR product. The authors found that the code 2 financing phenomenon for the Tapak Syariah iB KPR product tends to increase. From this phenomenon, the researchers found several problems, namely: (1) the causes or factors for the iB Syariah Tapak KPR customer with code 2 at Bank Sumut KCP Syariah HM Joni. (2) the impact of iB Syariah Tapak KPR customers with code 2 on the performance of Bank Sumut Syariah KCP HM Joni. and (3) the efforts or strategies of Bank Sumut Syariah HM Joni in the settlement of the iB Syariah Tapak KPR customer coded 2. The factors that led to the deterioration of Password 2 of some of these customers during 2021 were economic conditions related to the COVID-19 pandemic which was still ongoing in 2021, the relatively long Approval and Process for Submitting the OJK Stimulus Relaxation Program at Bank Sumut Syariah, along with other causes. . This research method uses descriptive qualitative method by means of direct field surveys and interviews. Based on the explanation above, the researchers conducted an analysis related to Financing Code 2 (In Special Attention) on KPR Products (House Ownership Loans) iB Syariah Tapak at PT. Bank Sumut Sharia Sub-Branch Office H.M Joni Medan.Keywords : Code 2 Financing, iB Syariah Tapak KPR Product